Development of a Project Based Arduino Uno R3- Assisted Robotic Training Design - Prasetyo, Zidan; Darmawan, Ilham Akbar; Desmira, Desmira (DPTE FT UNY, 2024)
This type of research and development aims to create designs and products for robotics training, as well as robotic training design feasibility through expert validation and eval-uation by respondents. Based on a survey of 49 people surveyed, 28.3% said they did not master the microcontroller material, 10.8% said they had learned it very well, and 17.4% said they didn't know. This suggests that a lower level of competence compared to the SKKNI makes robotics training necessary. A self-training model is used for this training. The study uses a branch version of the ADDIE development model, which is carried out in five stages: 1. analysis, 2. design, 3. development, 4. implementation, and 5. evaluation. This media produces starter kits and video learning, The ADDIE method is a research method that runs from the stage of analysis to its evaluation, the analysis researchers must know the gap of competence from students to industry, search for in-tuitive needs, make the need and the gap into the design of training until the last evalua-tion process, this is finally the reason why Addie is used in this research. Students of SMKN 1 Cilegon and students of Professional Education Electrical Engineering Universi-tas Sultan Ageng Tirtayasa were used in this research. The analytical techniques used are qualitative and quantitative descriptive analysis. Evaluation results from starter kits, learning videos, and learning materials are used to determine the level of eligibility for robotic training designs. The results of the starter kit evaluation showed that the media starter kit was in the category